The study of relationship between effective orientation program and employee readiness at Berjaya Golf Resort Berhad based on employee perception / Nur Khairul Bariyyah Awang Razalli - Awang Razalli, Nur Khairul Bariyyah (Faculty of Business and Management, 2020)
The purpose of this research is to study the relationship between effective orientation program and employee readiness in Berjaya Golf Resort Berhad. The aim of this study is to know the employee will become ready or not after the orientation program and which factor that more influence to them to be ready in performing their new work. This research study has six research objectives which are to identify the relationship between content of orientation program, duration of orientation program, trainer of orientation program and employee readiness. The next objectives is to identify relationship between effective orientation program and employee readiness, to determine factor that has most and least influence to the success of orientation program. The factor that are influence to success of orientation program is content, duration and trainer. In this study the most factor is trainer that make the employee become ready to perform their new job after the orientation program. This study was used correlation research method and the sample size was using Krejcie and Morgan (1970) table. Simple random sampling has been selected for this study in selecting the respondents. This study has been completed with a survey by using a form of questionnaire and the sample is among the employees in Berjaya Golf Resort Berhad. The finding show that, orientation program has strong relationship with employee readiness. Trainer and duration factor has moderate relationship towards employee readiness and content has negative relationship with employee readiness.